1982
DOI: 10.1007/bf00510355
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of histamine-induced itch and flare responses in human skin by the enkephalin analogue FK 33-824, ?-endorphin and morphine

Abstract: The effect of various opioid or putative neurotransmitter peptides on histamine-induced itch and flare responses was studied in humans after intradermal injection. Significant enhancement of the histamine responses was induced by the stable methionine-enkephalin analogue FK 33-824, beta-endorphin and morphine. The putative neurotransmitters substance P and vasoactive intestinal polypeptide (VIP)--which moreover are potent histamine liberators--had no enhancing effect. The potentiation induced by FK 33-824 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…Evidence increasingly suggests that endogenous opioids (endorphins) may be involved in transmission of itch. 22 …”
Section: Opioids and Endorphinsmentioning
confidence: 99%
“…Evidence increasingly suggests that endogenous opioids (endorphins) may be involved in transmission of itch. 22 …”
Section: Opioids and Endorphinsmentioning
confidence: 99%
“…Ninety per cent of consultant anaesthetists use inhalational agents for maintenance of anaesthesia in daycase laparoscopy patients, 50% do not employ any form of adjunctive local anaesthetic technique while a small proportion (6%) do not use NSAIDs wherever possible. Since the principal reasons for overnight admission following daycase gynaecological laparoscopy are pain, nausea and vomiting, dizziness and delayed mobilisation [3,4], we feel that these areas warrant further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Pruritus is a subjective unpleasant sensation arising from irritation of the nociceptor fibres in the superficial layers of the skin which provokes the urge to scratch. It is common following opioid administration and may be more unpleasant than the pain itself [1][2][3][4]. While pruritus has been reported following intravenous or intramuscular administration, it has been suggested that it is most common following intrathecal or epidural administration of opioids [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kallikrein and papain, however, elicit a burning itch without the release of histamine from dermal mast cells (32,33). Prostaglandins (34)(35)(36)(37) and endorphins (38,39) induce no or only weak itching on their own, but potentiate histamine-induced itching, i.e. they may act as peripheral modulators of itching.…”
Section: Mediators Of Itchingmentioning
confidence: 99%